Calamansi (Citrus microcarpa Bunge) flavored lemon grass (Cymbopogon citrates) juice - Marabe, Marigold Pilaro (2009.)
Five formulations of calamansi flavored lemen grass juice were prepared by varying the combination of lemon grass-water extract (LGWE) and pure calamansi extract (PCE).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Calamansi--Citrus microcarpa Bunge; Lemon grass--Cymbopogon citrates